Targeting LINC00707 by vitamin D3 attenuates nitrogen mustard-caused dermal toxicity through inhibiting ferroptosis - Xunhu Dong; Ying He; Xiaofeng Hu; Jie Wu; Feng Ye; Xiaogang Wang; Yuanpeng Zhao; Guorong Dan; Jiqing Zhao; He Tang; Xiaolu Lu; Yan Sai; et al. (Redox Biology)
Nitrogen mustard (NM) causes severe skin injury that is lack of effective and targeted therapies. Vitamin D3 (VD3) emerges as a promising treatment option for NM-caused dermal toxicity; however, the underlying mechanisms are currently unclear. Herein, we identified that NM markedly promoted ferroptosis by measurement of decreased cell viability, glutathione, glutathione peroxidase 4 and solute carrier family 7 member 11 levels, and increased ROS, lipid ROS, iron/Fe2+ and malondialdehyde contents in vitro and in vivo. Ferrostin-1 (Fer-1, a ferroptosis inhibitor) attenuated NM-caused cell death in keratinocytes. Meanwhile, NM significantly inhibited phosphorylation of AKT1 and glycogen synthase kinase 3β (GSK3β) and nuclear factor erythroid 2-related factor 2 (Nrf2) nuclear translocation, and increased LINC00707 expression. Furthermore, NM-induced ferroptosis in keratinocytes was abolished by treatment with agonists of Nrf2 (tBHQ) and AKT1 (SC79), the inhibitor of GSK3β (AR-A014418), Nrf2 overexpression or LINC00707 knockdown. Mechanistically, LINC00707 directly bound with the protein kinase domain of AKT1 and suppressed its phosphorylation and activated GSK3β thereby inactivating Nrf2, subsequently inducing ferroptosis and cell death in NM-treated keratinocytes. Moreover, VD3 notably suppressed LINC00707 expression, activated AKT1 and inactivated GSK3β, increased Nrf2 nuclear translocation and inhibited ferroptosis and cytotoxicity induced by NM in vitro and in vivo. The protective effects of VD3 against NM-caused dermal toxicity were blocked by erastin (a ferroptosis inducer), Nrf2 siRNA, LINC00707 overexpression and were enhanced by LINC00707 knockdown and Fer-1 in vitro and in vivo. In conclusion, VD3 ameliorated NM-caused dermal toxicity by inhibiting ferroptosis, which was partially mediated through the LINC00707-AKT1-GSK3β-Nrf2 signaling pathway.